LEGAL PROTECTION OF OUTSOURCING WORKERS FROM TERMINATION OF EMPLOYMENT UNDER LAW NUMBER 6 OF 2023 - Rr. Winarti Pudji Lestari; Muhamad Abas (Universitas Labuhanbatu, 2023)
In the increasingly fierce business competition, the outsourcing system is felt to be more effective for the company. On the other hand, the outsourcing system opens opportunities for employers to carry out Termination of Employment (PHK) actions easily. In the outsourcing system, there are weaknesses, there is no guarantee of continuity of work for workers. Law Number 6 of 2023 of Job Creation has regulated legal protection for outsourcing workers against arbitrary actions by employers in carrying out layoffs, through the principle of Transfer of Undertakings Protection of Employment (TUPE). But in practice, the TUPE principle is still not running effectively. The purpose of this research is to find out and understand the principles of the employment relationship between outsourced workers and employers so that unfair layoffs do not occur and legal protection for outsourced workers from employers' arbitrariness in implementing layoffs. This study uses a normative juridical approach. It is necessary to develop regulations regarding outsourcing in which legal protection for workers is further enhanced, determine sanctions and law enforcement for those who commit violations, and carry out more intensive supervision of the implementation of outsourcing.Â Keywords: Legal protection, outsourcing, continuity of work